Quality of Life in Caregivers of Patients with Schizophrenia: A Systematic Review of the Impact of Sociodemographic, Clinical, and Psychological Factors - Corina Gagiu; Vlad Dionisie; Mihnea Costin Manea; Anca Covaliu; Ana Diana Vlad; Ancuta Elena Tupu; Mirela Manea (Behavioral Sciences)
Caregiving for a patient with schizophrenia (PwS) imposes a high burden on caregivers and often affects their quality of life. This systematic review aims to synthesize the current evidence on the sociodemographic and psychological factors of caregivers, as well as patient-related sociodemographic and clinical factors, that may influence caregivers’ QoL. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive literature search was performed in three major databases—PubMed/Medline, SCOPUS, and Web of Science—to identify original studies examining informal caregivers of PwS and assessing the relationship between caregivers’ QoL and various sociodemographic, psychological, or clinical factors. Methodological quality appraisal was performed using the Joanna Briggs Institute checklist. In total, 31 studies were included in the review and discussed at length. Lower QoL was associated with unemployment, older age, female gender, financial difficulties, being unmarried, and lower education. Additionally, increased schizophrenia symptom severity, higher caregiver burden, and elevated levels of depression and anxiety may negatively influence caregivers’ QoL. Given these findings, future research should focus on developing tailored interventions to improve caregivers’ QoL. Addressing these modifiable risk factors through targeted support programs and policies could significantly enhance caregivers’ QoL.